2014
DOI: 10.1177/1077801213520580
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Neighborhood Income

Abstract: This investigation used a longitudinal design to examine the relationship between neighborhood-level income, individual-level predictors, and police-reported intimate partner violence in 5,994 urban couples followed over 2 years. At the baseline abuse incident, intimate partner violence rates were highest in the poorest neighborhoods (13.8 per 1,000 women in the lowest income quartile, followed by 12.1, 8.2, and 5.0 in the respective higher income quartiles). However, in the longitudinal analysis, weapon use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 70 publications
(166 reference statements)
3
37
1
Order By: Relevance
“…Our literature review identified nine studies on the associations between financial context and IPV perpetration. Three of those studies focused exclusively on male-perpetrated IPV as reported by the female victims (Bonomi et al 2014 ; Byun 2012 ; Golden et al 2013 ). Economic abuse, defined as behaviors that control a partner’s ability to be economically secure, is common among women who experience other forms of abuse (Adams et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our literature review identified nine studies on the associations between financial context and IPV perpetration. Three of those studies focused exclusively on male-perpetrated IPV as reported by the female victims (Bonomi et al 2014 ; Byun 2012 ; Golden et al 2013 ). Economic abuse, defined as behaviors that control a partner’s ability to be economically secure, is common among women who experience other forms of abuse (Adams et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Financial stress often impacts both individuals and the couple (Mason and Smithey 2012 ) and is a commonly cited antecedent to IPV perpetration (Byun 2012 ; Slep et al 2010 ; Neff et al 1995 ). However, IPV is not more prevalent in areas with low neighborhood income or high socioeconomic deprivation, which may be indicative of the financial stressors experienced by residents (Khalifeh et al 2013 ; Bonomi et al 2014 ). This difference in findings highlights the difference between stressors (the event) and stress (the response).…”
Section: Introductionmentioning
confidence: 99%
“…Urban informal settlements have been associated with high levels of poverty, crime and violence, poor health outcomes-including HIV/AIDS-as well as poor access to basic services such as schools and health care facilities. Past studies have found strong association between violence experience and poverty at the household [9,12] and community levels [9,13,14], a major characteristic of the urban informal settlements.…”
Section: Plos Onementioning
confidence: 99%
“…Due to the stressors created from living in impoverished Spanish Autonomous Community (AC) and attempting to regulate the disorder that is an inherent aspect of these neighborhoods, women experience higher IPV rates. 11 …”
Section: Introductionmentioning
confidence: 99%